94 Comparative benefit of olaparib in recurrent BRCAm ovarian, breast, pancreatic and prostate cancer. (13th November 2020) - Peters, P; Manrriquez, E; Amanam, I; Chan, J
Abstract : Objectives: To compare the extent of clinical benefit and cost effectiveness of olaparib in ovarian cancer compared to breast, pancreatic, and prostate cancer. Methods: Data were extracted from FDA labels for olaparib. We compared the use of olaparib in gBRCAm (germline BRCA mutant) recurrent ovarian, breast, prostate, and pancreatic cancer. Prevalence of the germline BRCA biomarker and survival benefit were compared between gynecologic and other cancer types. Incremental cost effectiveness ratio (ICER) analyses will be performed. Results: In ovarian cancer, 15–20% of patients carry gBRCAm. Treatment with olaparib at recurrence with gBRCAm increased PFS by 4.7 months progression-free survival (PFS) versus gBRCAwt (Study 19). In gBRCAm breast cancer, 10–15% of patients carry gBRCAm and had 2.8 month PFS benefit (OlympiAD). In pancreatic adenocarcinoma, gBRCAm is present in 9%, and POLO demonstrated a 3.6 months PFS benefit. Olaparib is approved for gBRCAm or homologous-recombination deficient (HRD) in metastatic castration resistant prostate cancer. With gBRCAm (present in 1–2% of patients), there was a 3.8 month of PFS benefit (PROfound), and 2.3 months including gBRCAm and HRD. Conclusions: Across cancer types with FDA approval for olaparib, the clinical benefit and proportion of patients eligible is highest in ovarian cancer. PFS benefit is similar across cancer types (2–5 month range). Prostate cancer is the only cancer with FDA approval for treatment with olaparib in the recurrent setting for both HRD and gBRCA. Additional study is on HRD breast, pancreatic, and ovarian cancer to determine if olaparib therapy could benefit these populations.